Design and Development Of Inorganic Fertilizer Packaging System With Iot-Based Tally Counter - Apriani, Akmecia Risqa; Yohandri, Yohandri (Department of Physics, Universitas Negeri Padang, 2023)
Inorganic fertilizers are fertilizers derived from chemical products produced by factories. This chemical, if inhaled, will seriously affect retail fertilizer sellers. Currently, sellers of diluted fertilizers still pack fertilizer manually, which takes a long time, as well as excessive labor and frequent fraud by employees against business owners and employees. The packaging system is engineering research aimed at determining the performance and design specifications of the system. The performance specification describes the performance of the packaging system, while the design specification describes the tool's sensor characteristics, accuracy, and precision. Data obtained through direct and indirect measurements. The direct measurement results are obtained from measuring the mass and detection distance of the packaging. In contrast, the indirect measurement results are obtained from the accuracy and precision of the tool. The results obtained on the system are performance specifications and tool design. The mechanical form of the device is obtained from the performance specifications. Then the system will detect the packaging that can be seen through the smartphone. The results obtained in this system are performance specifications and tool design. The mechanical form of the tool is obtained from the performance specifications. The system will measure the mass and detection distance of the packaging. The number of packaging can be seen through a smartphone. The accuracy of the packaging system to the mass is 99.82%, while the tool's accuracy to the mass is 99.52% which is obtained from the accuracy of measuring object 1.